Uji Aktivitas Ekstrak Daun Akasia (Acacia Auriculiformis) Sebagai Antihelmintik Terhadap Cacing Ascaris Suum - Stivani Jayanthi Beda; Nemay A Ndaong; Julianty Almet (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Ascariasis in pigs is a worm disease caused by Ascaris suum worms. These worms can cause a lot of losses that will have an impact on the production and growth of pigs. Control and treatment of Ascaris suum worms can be giving modern anthelmintics. However, the use of modern anthelmintics can have a negative impact. For that we need other alternative with herbal treatment using plants that have secondary metabolite compounds that are efficacious as anthelmintics such as acacia plants (Acacia auriculiformis). This study aimed to determine the effectiveness of extract leaves of acacia (Acacia auriculiformis) as anthelmintic against Ascaris suum worms and to determine the LC50 and LT50 values of extract leaves of acacia (Acacia auriculiformis). This research was conducted from July to August 2021. The sample of worms used was 105 tails for 3 replications using 7 groups consisting of 5 treatment groups test extract leaves of acacia (Acacia auriculiformis) concentrations of 5%, 10%, 15%, 20%, 25% and 2 control groups. The research data were analyzed using the Kruskal Wallis, Mann Whitney and probit analysis test. The results showed that within 7 hours of testing extract leaves of akasia (Acacia auriculiformis) was able to kill Ascaris suum worms at concentrations of 15%, 20% and 25% with LC50 value is 24.876% and LT50 is 7.083 hours.